An Analysis of Students’ Perception of Differentiated Content in Teaching Descriptive Text - Satriadi, Annisyaputri; Sunra, La; Baa, Sultan (Pascasarjana Universitas Negeri Makassar, 2025)
This study examines students' perceptions of content differentiation in teaching descriptive text at Negeri 1 Gowa High School. The study involved students of class X.2 with a qualitative approach through interviews, and observations. The results show that students generally perceive differentiated content positively. They believe that the use of visual media such as videos and images helps them better understand descriptive text. Gradually increasing the level of difficulty makes them feel more confident and less overwhelmed. Students also feel more motivated when the topics are interesting and delivered through interactive methods such as games, group discussions, and multimedia. Many students expressed their hope that teachers will continue to implement such engaging and personalized learning approaches in the future. For future research, it is recommended to examine the implementation or effectiveness of content differentiation in descriptive text materials and use contextual learning methods to increase students' understanding, enthusiasm and comfort in learning.